Effect of conflict and food price shocks on calorie intake and acute malnutrition in Nigeria: A micro-panel data analysis - Fadare, Olusegun; Akerele, Dare; Mavrotas, George; Ogunniyi, Adebayo (2019)
Food insecurity and malnutrition are being worsened in countries that are exposed to armed conflict. Nigeria has witnessed a decade of protracted armed conflict and civil unrest. Many civilians have died and some farming communities have been sacked as a result. This study uses fixed-effect and random-effect models on a nationally-representative household panel data– Nigeria Living Standard Measurement Survey and Armed Conflict and Event Location Data, to examine the linkages between conflict, food price shocks, and calorie intake and acute malnutrition (wasting) among children. The prevalence of calorie intake inadequacy and wasting increase across the years in conflict-prone areas. Empirical results suggest that increases in food prices, especially staples have a depressing effects on calorie intake and increasing influence on wasting prevalence. Surprisingly, there appears to be a decrease likelihood of wasting among households in conflict-prone areas despite relatively low level of calorie intake. This result may be indicative of access to certain nutrition-related non-food factors capable of reinforcing the available calorie intake in the areas. Although sensitively guided food pricing policy and prevention of conflicts are critical for improve calorie intake and nutrition outcome, greater reduction in wasting prevalence may be achieved if other nutrition-related factors are considered.